Determinants of Household Food Security in Pesisir Barat Regency - Dinda Clara; Arivina Ratih (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to analyze the determinants of household food security in Pesisir Barat Regency. The study uses secondary data from the March 2025 National Socioeconomic Survey (Susenas) with a total sample of 570 households. Household food security is measured using the Jonsson and Toole approach, which classifies households based on energy consumption adequacy. A binary logistic regression model is employed to examine the influence of socioeconomic factors on household food security. The results show that the gender of the household head, per capita expenditure, and household size have a significant effect on household food security. The gender of the household head and household size have a negative effect, while per capita expenditure has a positive effect. Meanwhile, employment status and savings ownership do not have a significant effect. The model demonstrates strong predictive performance, with an overall classification accuracy of 97.5% and a Nagelkerke R Square value of 0.771.